2006
DOI: 10.1024/0300-9831.76.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Supplementation with Ascorbate, Folate, and Vitamins B6 and B12 on Inflammatory Factors and Estrogen Levels in Obese Postmenopausal Women

Abstract: Little is known about the effects of commonly used vitamins on serum inflammatory markers and the hormonal balance in obese postmenopausal women. We studied the effects of an 8-week open-label supplementation with vitamins C (500 mg), B6 (25 mg), B12 (1 mg), and folate (5 mg) on C-reactive protein, interleukin-6, and estradiol levels in 20 obese (body mass index > or = 30) postmenopausal women. Outcomes were assessed in a blinded fashion. Folate and vitamin B12 levels rose significantly, suggesting that the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the Nurses' Health Study, among women with no prior history of CAD, users of multivitamins containing folate and vitamin B 6 had a reduced risk of CAD (56) . Very few human studies have been performed to evaluate the modifications of major markers of inflammation during supplementation with B vitamins, including vitamin B 6 , despite the association with either folate and/or vitamin B 12 (57,58) . Furthermore, results from these studies have shown that CRP and pro-inflammatory IL levels are unchanged after vitamin supplementation (57,58) .…”
Section: Vitamin B 6 Supplementation Inflammation and Cvd Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Nurses' Health Study, among women with no prior history of CAD, users of multivitamins containing folate and vitamin B 6 had a reduced risk of CAD (56) . Very few human studies have been performed to evaluate the modifications of major markers of inflammation during supplementation with B vitamins, including vitamin B 6 , despite the association with either folate and/or vitamin B 12 (57,58) . Furthermore, results from these studies have shown that CRP and pro-inflammatory IL levels are unchanged after vitamin supplementation (57,58) .…”
Section: Vitamin B 6 Supplementation Inflammation and Cvd Preventionmentioning
confidence: 99%
“…Very few human studies have been performed to evaluate the modifications of major markers of inflammation during supplementation with B vitamins, including vitamin B 6 , despite the association with either folate and/or vitamin B 12 (57,58) . Furthermore, results from these studies have shown that CRP and pro-inflammatory IL levels are unchanged after vitamin supplementation (57,58) . Antioxidant activity of vitamin B 6 supplementation has been observed in a study performed on rats, but the exact mechanism is unclear (59) .…”
Section: Vitamin B 6 Supplementation Inflammation and Cvd Preventionmentioning
confidence: 99%
“…On the basis that women have a higher Cbl level than men across age and race categories [71][72][73][74], female gender might be associated with neuroprotection and better clinical prognosis. An increment in serum estradiol caused by shortterm multi-vitamin supplementation including Cbl was reported from a study recruiting 20 postmenopausal women [75]. However, the biological interactions may vary according to exogenous or endogenous properties of sex hormone.…”
Section: Histopathologically Dwmhs But Not Pwmhsmentioning
confidence: 96%
“…With prenatal vitamins being recommended to women, and vitamin enrichment in a vast majority of processed foods, it can become all too easy to get into ranges of exposure to vitamins that may impact estrogen levels. Obese post-menopausal women experienced increases in serum E2 in response to supplementation with vitamins C, B6, B12 and folic acid [185]. Folic acid [102,103] and B12 [129] increase tissue response to estrogens.…”
Section: Environmental Endocrine Disruptorsmentioning
confidence: 99%